2021
DOI: 10.1186/s13756-021-00917-8
|View full text |Cite
|
Sign up to set email alerts
|

A large-scale investigation of alcohol-based handrub (ABHR) volume: hand coverage correlations utilizing an innovative quantitative evaluation system

Abstract: Background Current hand hygiene guidelines do not provide recommendations on a specific volume for the clinical hand rubbing procedure. According to recent studies volume should be adjusted in order to achieve complete coverage. However, hand size is a parameter that highly influences the hand coverage quality when using alcohol-based handrubs (ABHR). The purpose of this study was to establish a quantitative correlation between applied ABHR volume and achieved hand coverage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…Insu cient amount of ABHR applied for the hand size has been discussed as responsible for the poor dorsal coverage in many previous studies [17,18,19], and we also found that the ratio of the participants with insu cient dorsal coverage increased as the hands were larger. While taking our data, we also observed that many participants tended to focus more on rubbing the crotch of the ngers rather than the dorsal surface of the hand at the "palm over dorsum" step, which follows the ndings from the study by Durso et al [20].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Insu cient amount of ABHR applied for the hand size has been discussed as responsible for the poor dorsal coverage in many previous studies [17,18,19], and we also found that the ratio of the participants with insu cient dorsal coverage increased as the hands were larger. While taking our data, we also observed that many participants tended to focus more on rubbing the crotch of the ngers rather than the dorsal surface of the hand at the "palm over dorsum" step, which follows the ndings from the study by Durso et al [20].…”
Section: Discussionsupporting
confidence: 75%
“…The 1.1 ml ABHR used in our study could obtain a mean total coverage of over 90% for both sides of the hands, only for small hands. Voniatis et al reported that 3 ml is a reasonable volume for medium-sized hands [17], whereas Kenters et al reported that 2.25 ml is needed to cover both sides of the hands adequately (82-90%), although the hand size of the participants was not described in their report [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this study suggest that a volume of 1.5 mL ABHR is relative to be sufficient or not, depending not only on the size of the hands [ 37 ], but also the competency of the HCW, given the overwhelming effect of learning. HCWs having smaller hands are more likely to produce fine coverage, but the difference was non-significant.…”
Section: Discussionmentioning
confidence: 99%
“…According to the principal health agencies, ABHRs must contain at least 60%v/v alcohol, to have an effect as disinfectants on pathogens, including SARS-CoV-2 [8] . Scientific literature has evidenced that, in addition to the alcohols concentration, other factors that contribute to sanitation must be taken into account, such as the minimum friction time and the amount of sanitiser applied on the hands [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%